Implementasi dan Analisis Alat Kompres Demam Suhu Hangat dengan Sensor DS18B20 dan Pengendali Arduino Uno - Bachri, Karel Octavianus; Soewono, Arka; Kevin (Jurnal Elektro, 2024)
Fever is a condition where the body temperature rises above normal levels, often caused by an infection. Non-medical management of fever can be done by using cold or warm compresses. Warm compresses are more effective but require a complex and repetitive process. This study is the design of a Digital Fever Compress Device using warm temperature based on Arduino Uno. The Digital Fever Compress Device is designed for non-medical fever management. The Digital Fever Compress Device is equipped with a DS18B20 sensor, Liquid Crystal Display (LCD), Relay, cartridge heater as a heating element, three pushbuttons, XL4005 stepdown module, and one On-Off switch. The Digital Fever Compress Device can produce warm temperatures and adjust them according to the user's preferences with a minimum limit of 37.5°C and a maximum of 42°C with a timer for 20 minutes. Environmental temperature affects the temperature setting processing carried out by the microcontroller. Based on the tests conducted in an air-conditioned room, the average time from the initial temperature to the setpoint is 6 minutes and 15 seconds, and the temperature increase from the setpoint ranges from 45.6°C or 15.079%. Meanwhile, testing in a non-air-conditioned room, the average time from the initial temperature to the setpoint is 2 minutes and 26 seconds, and the temperature increase from the setpoint ranges from 44.64°C or 12.37%.